2022
DOI: 10.1021/acs.chemmater.1c03952
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Peroxidase-like Activity of Nitrogen-Doped Graphdiyne Oxide Quantum Dots/Gold–Silver Nanocage Heterostructures for Antimicrobial Applications

Abstract: Plasmon stimulation is an intriguing method to modulate the enzyme-mimic functions of nanomaterials, while utilization of plasmon excitation remains of low efficiency. Herein, by loading nitrogen-doped graphdiyne quantum dots (N-GDQDs) onto gold–silver nanocages (AuAg NCs), hollow cube-shaped N-GDQDs/AuAg NC heterostructures with strong local surface plasmon resonance (LSPR) response in the near-infrared (NIR) region are reported. This nanozyme can concurrently harvest LSPR-induced hot carriers and produce pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 54 publications
(55 reference statements)
2
46
0
Order By: Relevance
“…To date, with the rapid development of nanotechnology, a large number of antibacterial nanozymes have been developed, from noble-metal (e.g. Au [19][20][21][22][23][24][25][26], Pt [27], Cu [28], Ir [29], Ag [30], Au-Pt [31,32], Pd-Cu [33], Pd-Pt [34], Au-Ag [35], etc), transition metal oxide or sulfide (e.g. Fe 3 O 4 [36][37][38], CuO [39], CeO 2 [40], V 2 O 5 [41], Co-V mixed metal oxide (MMO) [42], MoS 2 [43][44][45][46][47], NiS 2 [48], CuS [49][50][51][52], Co 4 S 3 [53], MnO 2 [54] etc), and nanocarbon (e.g.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, with the rapid development of nanotechnology, a large number of antibacterial nanozymes have been developed, from noble-metal (e.g. Au [19][20][21][22][23][24][25][26], Pt [27], Cu [28], Ir [29], Ag [30], Au-Pt [31,32], Pd-Cu [33], Pd-Pt [34], Au-Ag [35], etc), transition metal oxide or sulfide (e.g. Fe 3 O 4 [36][37][38], CuO [39], CeO 2 [40], V 2 O 5 [41], Co-V mixed metal oxide (MMO) [42], MoS 2 [43][44][45][46][47], NiS 2 [48], CuS [49][50][51][52], Co 4 S 3 [53], MnO 2 [54] etc), and nanocarbon (e.g.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Actually, for NIR responsive metal-semiconductor hybrid nanozymes, the NIR excitation can not only induce local photothermal effect but also transfer of hot electrons simultaneously, of which the enzyme-like function is dominantly dependent on the hot electrons' transfer. Taking the gold-silver nanocages loaded nitrogen-doped graphdiyne quantum dots (N-GDQDs/AuAg NC) heterostructures as an example [35], as shown in figure 3(D), under NIR excitation, the N-GDQDs was induced to produce heat and hot carriers (e − ), which was then injected into AuAg, remarkably accelerating the decomposition of H 2 O 2 into •OH. Taking advantage of NIR-enhanced POD-like activity, the N-GDQDs/AuAg NC nanozyme possessed efficient broad-spectrum antibacterial activity under NIR irradiation.…”
Section: Nir Stimulationmentioning
confidence: 99%
“…For instance, hemin has been chosen as a functional molecule to improve peroxidase-like activity. Nanoparticles are also a good choice, such as Pd, PdFe, CeO 2 , and CuS . It has been reported that heteroatoms (N, B, and S) can enhance the enzymatic activity. Although great efforts have been made to improve the enzymatic activity and the application performance of GDY-based nanozymes, the understanding of their intrinsic properties or their enzyme-mimicking behavior is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…GDY-based quantum dots have attracted great attention due to the size effect. Since decreasing the size of carbon nanozymes is also an important way to improve the catalytic performance, , graphdiyne oxide quantum dots (GDYO QDs) with lateral sizes less than 100 nm were prepared through an oxidative cleavage method using concentrated HNO 3 in this work. The peroxidase-like activity of graphdiyne was greatly enhanced, which has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…Noble-metal nanoparticles (Ag, Au, etc.) have strong interactions with electromagnetic radiation, leading to the excitation of localized surface-plasmon resonance (LSPR) . LSPR have limited lifetimes and decay by radiatively emitting photons or nonradiatively generating electron–hole pairs. Recently, a considerable amount of work has been carried out on the hot carriers generated by LSPR’s nonradiative decay.…”
Section: Introductionmentioning
confidence: 99%